Post‐COVID‐19 internet addiction, depression, and pornography addiction among adolescents: Findings from a nationwide study in Bangladesh - Md Abu Bakkar Siddik; Irin Pervin; Md. Khalid Syfullah; Akher Ali; Al Mahmud; Mahedi Hasan; Sheikh Muzzammil Hussen; Monia Manjur; Zobayer Ahmed; Mohammad Meshbahur Rahman (Health Science Reports, 2024)
Abstract Background and Aims Regulations response to COVID‐19 has increased internet addiction (IA), depression, and pornography addiction (PA) among adolescents worldwide. The objective of this nationwide study was to assess the current prevalence rate of IA, depression, and PA after the post‐COVID‐19 period among school‐going adolescents in Bangladesh. Methods A total of 8832 male and female adolescents participated in this research. The cross‐sectional study was conducted online using a simple random sampling method. Including the sociodemographic variables, Young's IA Test (IAT‐20) Scale, Patient Health Questionnaire (PHQ‐9), and Pornography Craving Questionnaire (PCQ‐12) were used to measure IA, depression, and PA. By SPSS version 25.0, the prevalence and correlation between IA, depression, and PA were analyzed using the Chi‐square test, binary logistic regression, and a bivariate co‐relation matrix. Results Sixty‐three percent, 76.6%, and 62.9% of the students were suffering from IA, depression, and PA respectively. Depressive and anxious symptoms were significantly associated with IA. Female students were more depressed than males. Males were more addicted to pornography than females. Students who utilized social media but didn't exercise had greater depression and PA. IA, depression, and PA were correlated. Conclusion The research emphasizes the need for comprehensive mental health treatments, digital literacy programs, and family and teacher participation to reduce IA, depression, and PA among adolescents post‐COVID‐19. Promotion of physical exercise and supporting policies to build safer online settings for adolescents are also encouraged.